PENGARUH LEBAR SERAT ABAKA SEBAGAI MATERIAL NFRP UNTUK KUAT GESER BALOK BETON BERTULANG - Wirahman Salvana; Taufiq Saidi; Iskandar Hasanuddin; Muttaqin Hasan; Zahra Amalia (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2022)
Fiber Reinforced Polymer (FRP) is an alternative for planning, repairing, and strengthening structures. FRP is a combination of fiber as reinforcement and resin as adhesive. Reinforcing materials can be made of carbon, aramid, glass, and natural fibers. Utilization of Natural Fiber Reinforced Polymer (NFRP) FRP with natural fibers can be more economical. The natural fiber used in this research is abaca fiber which is often found and is not used for structural reinforcement. The purpose of this study was to determine the increase in shear strength of reinforced concrete beams with different widths of NFRP abaca fiber. NFRP Abaca fiber is fully wrapped (complete wrapping) on the surface of the reinforced concrete beam. The study was conducted on four reinforced concrete beams measuring 15 cm x 30 cm x 220 cm with simple support with two load points to determine the effect of abaca fiber width on increasing the shear strength of the beam. One specimen as a control test object and three specimens reinforced with Abaca Fiber NFRP with variations in fiber width of 2.5 cm, 5 cm, and 7.5 cm, respectively. The test results show an increase in the shear capacity of reinforced concrete beams as the fiber width increases. The flexural failure occurred in the test object with a width of 7.5 cm, this was the case that the shear capacity of the beam had exceeded the flexural capacity of the beam.